Serine Deficiency Exacerbates Inflammation and Oxidative Stress via Microbiota-Gut-Brain Axis in D-Galactose-Induced Aging Mice - Fengen Wang; Hongbin Zhou; Ligang Deng; Lei Wang; Jingqing Chen; Xihong Zhou (Mediators of Inflammation)
Inflammation and oxidative stress play key roles in the process of aging and age-related diseases. Since serine availability plays important roles in the support of antioxidant and anti-inflammatory defense system, we explored whether serine deficiency affects inflammatory and oxidative status in D-galactose-induced aging mice. Male mice were randomly assigned into four groups: mice fed a basal diet, mice fed a serine- and glycine-deficient (SGD) diet, mice injected with D-galactose and fed a basal diet, and mice injected with D-galactose and fed an SGD diet. The results showed that D-galactose resulted in oxidative and inflammatory responses, while serine deficiency alone showed no such effects. However, serine deficiency significantly exacerbated oxidative stress and inflammation in D-galactose-treated mice. The composition of fecal microbiota was affected by D-galactose injection, which was characterized by decreased microbiota diversity and downregulated ratio of Firmicutes/Bacteroidetes, as well as decreased proportion of Clostridium XIVa. Furthermore, serine deficiency exacerbated these changes. Additionally, serine deficiency in combination with D-galactose injection significantly decreased fecal butyric acid content and gene expression of short-chain fatty acid transporters (Slc16a3 and Slc16a7) and receptor (Gpr109a) in the brain. Finally, serine deficiency exacerbated the decrease of expression of phosphorylated AMPK and the increase of expression of phosphorylated NFκB p65, which were caused by D-galactose injection. In conclusion, our results suggested that serine deficiency exacerbated inflammation and oxidative stress in D-galactose-induced aging mice. The involved mechanisms might be partially attributed to the changes in the microbiota-gut-brain axis affected by serine deficiency.